The Role of state in the development of construction companies - Mammadova Kamala Mehdi, (Technium Social Sciences Journal, 2020)
The purpose and objectives of the study are to identify the role of the state in the development of construction companies and to define the economic mechanisms of the mutual relationship of internal and external factors for increasing the efficient management of the construction companies. Comparative analysis, a logical-systematic approach, comparison and generalization, analysis and synthesis, and economic and statistical methods were used in the course of research. The scientific novelty of the study aims at identifying the economic principles of the strategic management of construction companies, determining the relationship between internal and external factors, evaluating the advantage of the advanced management methods, and assessing the role of the state in the management of construction companies. Conclusion. The main role of internal and external factors in the development of construction companies is to protect them from the monopolistic sources of threats and increase their competitiveness in both domestic and global markets. The internal and external factors in the management of construction companies are mutually interconnected. The major factors contributing to the development of these relations depend on the use of information technology, innovation, and the economic policy pursued by the state.